Design and Development of Game Based Learning Applications for Mathematics Learning Based on Multiple Language to Develop Verbal Capabilities - Muhammad Syifa’ul Qolbi; Zahid Zufar At Thaariq; Sayyidati Fatimah Az-Zahroh; M. Mahfudz Anwar; Nurul Faiza (JPP (Jurnal Pendidikan dan Pembelajaran), 2019)
The purpose of this research is to design an application that can help students in learning. So, the authors are interested in designing game-based mobile learning applications that have mathematical content on integer material integrated with hijaiyah numbers, so that the game media has its own uniqueness. This design is based on the obligation to develop numeracy skills for all citizens according to Law number 20 of 2003 concerning the national education system. In addition, there is also an obligation to understand the number of hijaiyah for Muslim citizens. The research method used uses research development. The development model used is Lee Owens. The concept in this game is like a game in general that uses this type of adventure. In the game there is a mission to solve the problem. The challenge is through hijaiyah figures provided. So this game combines mathematics with hijaiyah numbers in a portable way.